Critical Review of Marketing Mix, Brand Equity on Restaurant Consumer Purchasing Decisions - Raharjo, Tri (Borong Newinera Publisher, 2025)
The success of the marketing campaign of “Share a Coke With” has been globally known as one of the personalized campaigns with some popular individual names. This act of corporate communication has made the Coca-Cola Company even stronger as a multinational company. The usage of individual names has created a stronger bond between the brand and the audience. This qualitative research examines to what extend the brand image of Coca-Cola has affected the perception of its audience as it will have the implications of the economic and the social effects to the brand. The qualitative approach is used through the content analysis technique to some residents who were born and raised in Surabaya as of 2024, with 6 participants participating by the purposive sampling. This research examines the brand image by its favourability, strength, and uniqueness associated to Coca-Cola as a brand. Results has indicated a significant influence to the brand image and the personalized campaign. This research has underscored the importance in building consumer relations, strengthening the marketing strategy, and shaping brand image in a more complex world full of messages.